Measuring Mindfulness in one minute or less: A 10-item short version of the Five Facet Mindfulness Questionnaire (FFMQ) in Indonesian - Fourianalistyawati, Endang; Listiyandini, Ratih Arruum; Sahidah, Titi; Kumalasari, Dewi; Grasiaswaty, Novika (Fakultas Psikologi Universitas YARSI, 2023)
The Five Facet Mindfulness Questionnaire (FFMQ) is a scale to measure a person's level of mindfulness. FFMQ has been used extensively in other countries. In multi-construct research, a scale with fewer items is needed but with a qualified psychometric value. The purpose of this study was to obtain a short version of the Indonesian FFMQ which has good psychometric properties. The research was carried out in three stages, namely the adaptation stage, the long form test stage and then the short form test. The sample of this study is Indonesian people who are over 15 years old. The results show that the short form has shown good results. This indicates that the short form version of FFMQ Indonesia has good psychometric properties.